Immunopathology of the renal vascular lesion of progressive systemic sclerosis (scleroderma). - Lapenas, D. (1978)
Patients with progressive systemic sclerosis (PSS, scleroderma) exhibit a variety of immunologic abnormalities. To verify whether the renal vascular lesions of such patients might be mediated by an immunologic mechanism, kidney tissues of 16 patients with PSS were investigated by means of fluorescence, light, and electron microscopy; elution of tissue-bound antibody; and fixation of heterologous (guinea pig) complement. Controls consisted of 12 nonsclerodermatous patients with similar levels of hypertension with no evidence of associated immunologic abnormalities. Diffuse vascular deposits of immunoglobulins (predominantly IgM) and/or complement (predominantly Clq) were found in all 16 patients with PSS. These deposits were bound to the intima of intralobular and arcuate arteries which, by light microscopy, often exhibited typical fibromucinous alterations. Elution of antibody and heterologous complement fixation studies suggested that such reactants may represent the interaction of complement-fixing antibody and antigen. Electron microscopies studies demonstrated abundant fibrillar and ground substance material in the arterial intima but features of deposited (circulating) immune complexes were not found. By contrast, in the hypertensive (control) group, deposits of immunoglobulin (s) and/or complement were rare and, when present, were mostly confined to the arterioles. As judged by the results of elution and heterologous complement fixation, these arteriolar deposits appeared to represent trapped rather than specifically bound serum proteins. The possible signficance of these findings are discussed in relation to immunologic mechanisms which might be implicated in the pathogenesis of the renal vascular disease of PSS.